The Influence of Formal and Informal Sanctions on Offending: The Moderating Role of Legal Cynicism - Heitkamp, Amanda (Crime & delinquency, 2024)
Work on deterrence demonstrates that high perceptions of formal sanctions (e.g., arrest) and informal sanctions (e.g., negative reactions from others) both relate to decreased offending behaviors. However, there are numerous contextual factors that influence the strength of formal and informal sanctions on crime. The current study uses the Pathways to Desistance data to explore how formal and informal sanctions relate to offending, and how legal cynicism moderates this process. Findings from a series of longitudinal models show that higher perceptions of both formal and informal sanctions are related to decreased offending, while higher legal cynicism is linked to increased offending. Legal cynicism moderates the relationship between formal—but not informal—sanctions and offending. Policy implications are explored.